2019
DOI: 10.1007/s13313-019-00666-8
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum, Ganoderma australe, and bacterial wetwood as predictors of ironwood tree (Casuarina equisetifolia) decline in Guam

Abstract: Ironwood (Casuarina equisetifolia subsp. equisetifolia) trees on Guam have been in decline since 2002. This study applied proportional odds logistic multiple regression modeling to a set of biological variables in order to find significant decline predictors as a first step towards identifying pathogenic contributors. Based on the analysis of a set of 77 medium and large trees, the bacterium Ralstonia solanacearum and the fungus Ganoderma australe species complex were found to be significant predictors, with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Casuarina equisetifolia (ironwood) trees in Guam are dying in large numbers due to ironwood tree decline (IWTD) since 2002 [ [4] , [5] , [6] , [7] ]. Bacteria such as the bacterial wilt pathogen Ralstonia solanacearum and wetwood bacteria of the genus Klebsiella ( Klebsiella oxytoca and Klebsiella variicola ) were identified in the ooze of declining trees and considered as predictors of IWTD [ 6 , 7 , 2 , 8 ]. The presence of termites was found to be significantly associated (p<0.01) with IWTD [1] and termites are known to harbor a large bacteria diversity [9] .…”
Section: Objectivementioning
confidence: 99%
“…Casuarina equisetifolia (ironwood) trees in Guam are dying in large numbers due to ironwood tree decline (IWTD) since 2002 [ [4] , [5] , [6] , [7] ]. Bacteria such as the bacterial wilt pathogen Ralstonia solanacearum and wetwood bacteria of the genus Klebsiella ( Klebsiella oxytoca and Klebsiella variicola ) were identified in the ooze of declining trees and considered as predictors of IWTD [ 6 , 7 , 2 , 8 ]. The presence of termites was found to be significantly associated (p<0.01) with IWTD [1] and termites are known to harbor a large bacteria diversity [9] .…”
Section: Objectivementioning
confidence: 99%
“…The disease can cause up to approximately 80% growth reductions, leading to reduced pulp production and considerable economic losses (Ferreira et al, 2017). It has recently been reported that R. solanacearum causes bacterial wilt in ironwood trees in Guam (Ayin et al, 2019).…”
Section: Ralstonia Solanacearum Species Complexmentioning
confidence: 99%
“…It has recently been reported that R . solanacearum causes bacterial wilt in ironwood trees in Guam (Ayin et al, 2019). The third species, R .…”
Section: Phages For Treatment Of Bacterial Tree Diseasesmentioning
confidence: 99%
“…A variety of pathogenic bacteria have been isolated from wet heartwood tissues. Strains of Enterobacteriaceae are most often isolated from diseased trees, particularly Erwinia and Klebsiella, as well as Enterobacter, Pantoea, Citrobacter, Edwardsiella, Lactobacillus, and Kosakonia (Carter, 1945;Hartley et al, 1961;Knutson, 1973;Schink et al, 1981b;Murdoch, 1983;Diamandis and Koukos, 1992;Zheng et al, 2006;Ayin et al, 2019;Goychuk et al, 2020). Other bacteria are also often separated from the wet heartwood of conifers and broadleaf trees, such as Bacillus, Clostridium, Bacteroides, Ralstonia, Xanthomonas, and Pseudomonas (Carter, 1945;Knutson, 1973;Schink et al, 1981b;Murdoch, 1983;Warshaw et al, 1985;Diamandis and Koukos, 1992;Kovaleva et al, 2015;Ayin et al, 2019;Goychuk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…I-69/55 ( Yu et al, 2019 ), Betula pendula roth ( Goychuk et al, 2020 ), Ulmus spp. L. ( Alizadeh et al, 2017a , b ), Morus ( Basavand et al, 2021 ), Casuarina equisetifolia ( Ayin et al, 2019 ), Gmelina arboreaI ( Moya et al, 2009 ), and other broad-leaved tree species. Many things have been investigated to identify the causes for development of wetwood, such as genetic variability, bacterial and fungal communities, wood physicochemical properties, and wood processing and utilization ( Schroeder and Kozlik, 1972 ; Schink et al, 1981a ; Xu et al, 2001 ; Jeremic et al, 2004 ; Zhang et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%